Quality Evaluation on Private Higher Education Institutions in Pekanbaru (Integrating Kano Model and Quality Function Deployment) - Purwati, Astri Ayu; Sitompul, Silvia Sari (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
The era of ASEAN Economic Community (AEC) requires all higher education institutions in Asia should be ready to compete each other so the alumni can fulfill the requirements in ASEAN labor market. The purpose of this research is to evaluate the quality of higher education institutions (HEI) in Pekanbaru based on student sperceptions and to provide some technical responses to result in quality improvement. Samples of this research are seven (7) private universities which were selected by using cluster sampling method with 379 students of the total respondents. This research also used Kano Model and Quality Function Deployment approach as the integration tools which can help togather voice of customer (VoC) and generate a matrix of priority needs and technical responds in a form of House of Quality. The result of this research found 9 (nine) priority on need. They are studentâs achievement index which is more than 3.00, research supervising by the lecturer, lecturerâs discipline, ability of the use of technology, lecturerâs assesment method, academic staffâs passion and patience in delivering service, english proficiency, teaching and learning atmosphere, academic Information Effectiveness. From this research, HEI can conduct several steps to improve the quality such as lecturer and staffâs training and development, monitoring of teaching and learning process, studentâs softskill and practical ability improvement, and monitoring of academicâs rules and procedures.